Rome, Italy. The brickstamps of the Domus Tiberiana from the Archive of Clemens Krause. Season 2020 - Bukowiecki, Evelyne; Mimmo, Milena; Perotta, Francesco (e-Forschungsberichte des DAI, 2021)
This article presents the results of two short scholarships on the important collection of brick stamps collected by Professor Clemens Krause (University of Fribourg, Switzerland) and his team during their study of the Domus Tiberiana between 1981 and 1987. The work stands in line with the research carried out by Ulrike Wulf-Rheidt and Evelyne Bukowiecki on the brick stamps of other imperial residences of the Palatine in the framework of the »Palatin-Projekt«. By entrusting his archive to the authors, Krause intended to make the most of this unpublished collection. This preliminary study should thus be interpreted as a first step towards making these data available for further research on brick stamps as indicators of the supply dynamics of building sites and construction processes in imperial Rome.